Conflicting logics for crisis management in tourism. Issue 3 (30th June 2021) - Öberg, Christina
Abstract : Purpose: In tourism research, crisis management mostly refers to operational, on-location, chaotic measures taken as a crisis strikes a tourism destination. Related to COVID-19, this paper focuses on public initiatives representing strategic-oriented crisis management while showing that such initiatives may not help those needing support. More precisely, the paper discusses and exemplifies the conflict of logics between private sector interests and public initiatives related to crisis management in tourism. Design/methodology/approach: The main data source is a structured newspaper review of COVID-19 and tourism as covered in the Swedish press, comprising more than 4, 000 items. Findings: Findings indicate logics manifested at different levels and a logic gap between small and large firms. Large firms are potentially better able to adapt but tend to wait passively for financial support rather than reformulate their business operations. Originality/value: The paper contributes to research on crisis management in tourism by taking a public, societal-level view of crisis management juxtaposed against the local actors' sphere of operations. The conflict of logics proves how support needs to be improved to better help a sector in crisis. Thematic logics are introduced as a concept and captured in the conflicts between the present and the future, survival and change and operations and aggregates in crisis management. Broadly, the paper provides valuable insights into the future of tourism while indicating policy failures in the sector.